The impact of transmission learning style exercise my skills serial transmission between front-facing and beating the overwhelming volleyball - Khalil, Amar (Journal of Physical Education, 2010)
The research contain five chapters, the first chapters contain the introduction and it’s how importance it is, a review been taken on the matter of learning the exercises, and how the selection of a particular exercise should be fit with the ability of the learner and their level of handling the practice, according to that will estimate the qualifications and give the kind of level to get used of it to learn kind of talent some how similar to the basic one in order to response and comprehend the matter, and result of this process will save more time in learning the new talent plus the ex experience ,gather it together to signed to be more creative in the future in the learning practicing methods. The more importance point in this research in using a structure or tabling to organizing the serial exercise then compare it with the used methods in learning the volleyball, such as serving talent, then transferring in learning and profession of the super hit. About the searching matter the researcher have found a fact that teachers maybe needs more preparations, perfect planning, in order to send and teach the perfect learning and to spend less time in this process, because there is a weakness in the technical playing specially the super hit, there for the hole matter needs tabling the exercises to fit with the new learners ,that’s why the researcher put the goals and the purposes according to the research title as its been specified the human, mechanic and timing levels. In the second chapter contain the ways of learning and practicing the two moves, plus the transitional methods and the approving after the learning process, also explaining the qualification talents in the research. The third chapter contain the educational details in the research, the researcher used the experimental subject to achieve the on the field procedure search. The forth chapter contain showing the results in tables shapes, and mathematic ways, according to the procedures statistics. The final chapter, fifth one contain the recommendations final results